Corrosion and tribocorrosion behaviour of Al-Si-Cu-Mg alloy and its composites reinforced with B4C particles in 0.05 M NaCl solution - Toptan, F.; Alves, A. C.; Kerti, I.; Ariza, E.; Rocha, L. A. (ELSEVIER SCIENCE SA, 2013)
The corrosion behaviour of metal matrix composites (MMCs) is strictly linked with the presence of heterogeneities such as reinforcement phase, microcrevices, porosity, secondary phase precipitates, and interaction products. Most of the literature related to corrosion behaviour of aluminium matrix composites (AMCs) is focused on SiC reinforced AMCs. On the other hand, there is very limited information available in the literature related to the tribocorrosion behaviour of AMCs. Therefore, the present work aims to investigate corrosion and tribocorrosion behaviour of Al-Si-Cu-Mg alloy matrix composites reinforced with B4C particulates. Corrosion behaviour of 15 and 19% (vol) B4C reinforced Al-Si-Cu-Mg matrix composites and the base alloy was investigated in 0.05 M NaCl solution by performing immersion tests and potentiodynamic polarisation tests. Tribocorrosion behaviour of Al-Si-Cu-Mg alloy and its composites were also investigated in 0.05 M NaCl solution. The tests were carried out against alumina ball using a reciprocating ball-on-plate tribometer. Electrochemical measurements were performed before, during, and after the sliding tests together with the recording of the tangential force. Results suggest that particle addition did not affect significantly the tendency of corrosion of Al-Si-Cu-Mg alloy without mechanical interactions. During the tribocorrosion tests, the counter material was found to slide mainly on the B4C particles, which protected the matrix alloy from severe wear damage. Furthermore, the wear debris were accumulated on the worn surfaces and entrapped between the reinforcing particles. Therefore, the tendency of corrosion and the corrosion rate decreased in Al-Si-Cu-Mg matrix B4C reinforced composites during the sliding in 0.05 M NaCl solution. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Metal-matrix composite; Corrosion-wear; Wear testing; SLIDING WEAR BEHAVIOR; ALUMINUM-MATRIX COMPOSITES; CERAMIC PARTICLES; GRAIN-REFINEMENT; RESISTANCE; COATINGS; MICROSTRUCTURE; SOLIDIFICATION; MECHANISMS; AA6061; Engineering; Materials Science